AVALIAÇÃO DO ALCANCE FUNCIONAL DE INDIVÍDUOS COM LESÃO MEDULAR ESPINHAL USUÁRIOS DE CADEIRA DE RODAS (Movimenta (ISSN 1984-4298), 2018)
Medullar lesions consists in any type of trauma that causes motor and/or sensorial disturbs. The aim of this study was to evaluate the functional reach in paraplegic individuals, users of wheelchairs, as well as the influence of preservation of partial or total abdominal muscles. For that, 13 participants diagnosed with paraplegia, mean age 37 ± 11 years, users of a wheelchair for at least one year, were divided into two groups: G1 (levels above T8) and G2 (levels below T8). All the subjects were submitted to the Functional Reach Test, adapted to the sitting position. The statistical analysis consisted by the non-parametric test Mann Witney-U test, with a significant level of 5% (p